2011
DOI: 10.2174/156802611794863599
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Structural Investigations on Kynurenine Aminotransferase II: An Example of Conformation-Driven Species-Specific Inhibition?

Abstract: Kynurenic acid (KYNA), one of the metabolites belonging to the kynurenine pathway, has been described as an important neuroprotective compound, its unbalancing being associated with several pathological conditions. In human brain, the majority of KYNA production is sustained by kynurenine aminotransferase II (KAT II). A selective KAT II inhibitor would be an important pharmacological tool, since it would reduce KYNA formation without causing complete depletion of this neuroprotector. (S)-(4)-(ethylsulfonyl)ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…It has been supposed that this difference in inhibitory activity may arise from the presence in the catalytic site of human KATII of two hydrophobic residues, Leu40 and Pro76, which are replaced by polar serines in the rat enzyme [57]. Recently [114], a human KATII double mutant harboring the serines characterizing the rat ortholog active site was generated in order to investigate the molecular basis for ESBA species specificity. The site-directed mutagenesis approach did not provide any experimental support to explain the striking difference in ESBA inhibitory efficiency towards rat and human KATII, and underlined the need for more in-depth biochemical investigations aimed at deciphering the mechanism of ESBA inhibition.…”
Section: Esba and Csa -Inhibitors And/or Substrates?mentioning
confidence: 99%
“…It has been supposed that this difference in inhibitory activity may arise from the presence in the catalytic site of human KATII of two hydrophobic residues, Leu40 and Pro76, which are replaced by polar serines in the rat enzyme [57]. Recently [114], a human KATII double mutant harboring the serines characterizing the rat ortholog active site was generated in order to investigate the molecular basis for ESBA species specificity. The site-directed mutagenesis approach did not provide any experimental support to explain the striking difference in ESBA inhibitory efficiency towards rat and human KATII, and underlined the need for more in-depth biochemical investigations aimed at deciphering the mechanism of ESBA inhibition.…”
Section: Esba and Csa -Inhibitors And/or Substrates?mentioning
confidence: 99%
“…Involvement of kynurenic acid in these neurochemical and behavioural effects of ESBA were prevented by the simultaneous administration of kynurenine or kynurenic acid itself. Unfortunately, later work indicated that ESBA was much less active as an inhibitor of the human KAT enzyme because of a higher molecular flexibility in the region of the substrate binding site (Casazza et al ., ).…”
Section: Drug Developmentmentioning
confidence: 97%
“…Additionally, recent reports have established that sequence variants in human and rat KAT II cause significant cross-species enzyme potency shifts for inhibitor 4. 19,20 Our primary objective was to identify a selective, brain-penetrant tool compound for further exploration of KAT II inhibition in preclinical models of schizophrenia and cognition. Identification of a series of KAT II inhibitors with submicromolar binding affinity at both the rat and the human isoforms of KAT II would facilitate preclinical studies and clinical candidate identification.…”
mentioning
confidence: 99%
“…Several recent studies have employed the selective tool compounds ( S )-ESBA ( 4 ) and BFF-122 ( 5 , Figure ) via central administration for study of KAT II inhibition in preclinical models. However, identification of brain-penetrant KAT II inhibitors with druglike properties remains a challenge. Additionally, recent reports have established that sequence variants in human and rat KAT II cause significant cross-species enzyme potency shifts for inhibitor 4 . , Our primary objective was to identify a selective, brain-penetrant tool compound for further exploration of KAT II inhibition in preclinical models of schizophrenia and cognition. Identification of a series of KAT II inhibitors with submicromolar binding affinity at both the rat and the human isoforms of KAT II would facilitate preclinical studies and clinical candidate identification.…”
mentioning
confidence: 99%